1999: Overview - M Biggiogera (European Journal of Histochemistry)
In the last year of the century (or, better, the last of the years beginning with 19...) the European Journal of Histochemistry has published four issues and three Supplements for a total of 576 pages. In the Supplements 313 abstracts are collected. In the four issues 34 papers appear, of which 31 are original paper while the remaining three are minireviews. Supplements first: in the first are collected the papers presented at the First International Conference on the “Analysis of microbial cells at the single cell level. Why, How, When?” held in Como, Italy on March 25th to 27th, on behalf of the Micro Physiology Section of the European Federation of Biotechnology, of the Federation of European Microbiological Societies, the Società Italiana di Microbiologia generale e Biotecnologie Microbiche and the Italian Group of Cytometry.